Portuguese cultural adaptation and validation of the European Health Literacy Survey (HLS-EU) for children aged 9 to 10 (HLS-EU-PTc). (13th November 2019) - Saboga-Nunes, L; Dias, H; Andrade, C; Okan, O; Bollweg, T; Carvalho, G; Bittlingmayer, U
Abstract: Introduction: To measure Health literacy (HL) as proposed in the context of the European Health Literacy Survey/questionnaire (HLS-EU-Q), the Health Literacy for Children and Adolescents (HLCA) Consortium (GE) adapted it for children. A trans-cultural adaptation and validation to Portuguese (HLS-EU-PTc), will supply policy makers, experts and health professionals with information that can promote healthier communities while fighting health disparities. Methods: After permission was granted from the HLCA Consortium the TRAPD model was used (eg parallel translation, focus groups, two back translations). An assessment and pretesting of HLS-EU-PTc was done with 16 children for cognitive testing. A qualitative explanatory (n = 16) and quantitative, cross-sectional study (n = 82), age mean 13, SD 0.96, from Portugal (mainland) was implemented for proceed with the validation process. A variety of measures were obtained like internal consistency and mean scores. Results: Preliminary results for evaluation of the psychometric properties of the HLS-EU-PTc show satisfactory internal consistency (Cronbach's alpha coefficient 0.87). In a scale from 1 (very difficult) to 4 (very easy) for indicators of the HLS-EU-PTc, we have a mean of 3.25 and a SD of .478. Conclusions: This is the first study to examine the feasibility of a Portuguese version (HLS-EU-PTc) of the HLS-EU-Q adapted for children and it indicates high internal consistency and level of self-reported HL. The usefulness of the HLS-EU-PTc instrument can be further discussed while planning public health policy strategies from the HL standpoint. The validated HLS-EU-PTc version of the HLS-EU-Qc survey, with the user's manual can be accessed at www.literacia-saude.info .